Antigen-Specific CD4+ T-Cell Activation in Primary Antibody Deficiency After BNT162b2 mRNA COVID-19 Vaccination - Sauerwein, Kai M. T.; Geier, Christoph B.; Stemberger, Roman F.; Akyaman, Hüseyin; Illes, Peter; Fischer, Michael B.; Eibl, Martha M.; Walter, Jolan E.; Wolf, Hermann M. (Frontiers in Immunology, 2022)
Previous studies on immune responses following COVID-19 vaccination in patients with common variable immunodeficiency (CVID) were inconclusive with respect to the patients´ ability to produce vaccine-specific IgG antibodies, while patients with immunoglobulin isotype deficiency or selective antibody deficiency (oPAD) have not been studied at all. In this study we examined antigen-specific activation of CXCR5-positive and CXCR5-negative CD4+ memory cells as well as isotype-specific and functional antibody responses in patients with CVID as compared to other, milder forms of primary antibody deficiency (oPAD) and healthy controls six weeks after the second dose of BNT162b2 vaccine against SARS-CoV-2. Expression of the activation markers CD25 and CD134 was examined by multi-color flow cytometry on CD4+ T cell subsets stimulated with SARS-CoV-2 spike peptides, while in parallel IgG and IgA antibodies as well as surrogate virus neutralization antibodies against SARS-CoV-2 spike protein (S) were measured by ELISA. The results show that in CVID and oPAD normal IgG responses (titers of S-specific IgG three times the detection limit or more) were associated with intact vaccine-specific activation of CXCR5-negative CD4+ memory T cells, despite defective cTfh activation. In contrast, CVID IgG nonresponders showed defective vaccine-specific and superantigen-induced activation of both CD4+T cell subsets. In conclusion, impaired TCR-mediated activation of CXCR5-negative CD4+ memory T cells following stimulation with vaccine antigen or superantigen identifies patients with primary antibody deficiency and impaired IgG responses after BNT162b2 vaccination.